A study on the convergence of observer-based kinetics estimators in stirred tank bioreactors - Oliveira, R.; Ferreira, E.C.; Oliveira, F.; Feyo de Azevedo, S. (Journal of process control, 1996)
This paper is devoted to the tuning problem of an observer-based algorithm for the on-line estimation of reaction rates in stirred tank bioreactors. The relation between the dynamics of convergence and the tuning procedure is explored. The method proposed imposes a variable second-order dynamics on the convergence of the estimator. This approach is shown to compare favourably with a pole placement based technique, in an application to a baker's yeast fed-batch fermentation.